Electrical and temperature characterisation of silicon and germanium nanowire transistors based on channel dimensions - Hani Taha, Abd Assamad Al Ariqi (2020)
Amongst various sensing and monitoring technologies, sensors based on field effect transistors (FETs) have attracted considerable attention from both the industry and academia. Owing to their unique characteristics such as their small size, lightweight, low cost, flexibility, fast response, stability and ability for further downscaling, nanowire transistors (NWTs) can serve as ideal nanosensors and successors to FET-based nanoscale devices. However, as the dimensions (length, diameter and oxide thickness) of NWT channels are shrinking down, the electrical and temperature characteristics of NWTs are affected, thereby degrading the transistor performance. Although the applications of NWTs as biological and/or chemical sensors have been extensively explored in the literature, the use of these transistors as temperature sensors has been largely ignored. Consequently, this research investigates the impact of the cross-sectional dimensions of silicon nanowire transistors (SiNWTs) and germanium nanowire transistors (GeNWTs) on their electrical and temperature characteristics. Accordingly, evaluate and compare the performance of the considered nanowires and their potential applicability as temperature nanosensors for continuous temperature monitoring with good detection capability, high flexibility and low cost. A comprehensive simulation-based comparative study is performed by using six variable parameters, namely, gate length (Lg), channel diameter (Dch), oxide thickness (Tox), ambient temperature (T), gate bias voltage (Vg) and drain bias voltage (VDD). The impact of changes in these parameters on the electrical and temperature characteristics of SiNWTs and GeNWTs is then evaluated. The well-known MuGFET simulation tool for nanoscale multi-gate FET structure is used for the experimental simulations. A wide range of variable parameters are simulated in three simulation-based case studies, which cover 21 operating voltages and an ambient temperature increasing from 225 K to 450 K by a step of 25 K. The first case study considers the variation in gate length (Lg = 25, 45, 65, 85 and 105 nm), the second focuses on the variation in channel diameter (Dch = 10, 20, 40 and 80 nm) and the third focuses on the variation in channel oxide thickness (Tox = 1, 2, 3, 4 and 5 nm). Four performance evaluation metrics are considered, namely, subthreshold swing (SS), threshold voltage (Vth), drain-induced barrier lowering (DIBL) and drain current variation rate, ∆Id, which serves as an indicator of temperature sensitivity. The optimal stability- and sensitivity-based performance of NWTs can be achieved at certain optimal operating voltages with the SS values closer to the ideal state, a lower DIBL level and higher voltage threshold values. The simulation results for SiNWTs and GeNWTs highlight the effects of varying the channel dimensions (Lg, Dch, and Tox) on their temperature and electrical characteristics. Specifically, the temperature sensitivity (∆Id) of SiNWTs and GeNWTs significantly increased along with various channel dimensions and operating temperatures, and the optimal operating voltages are identified for each NWT. According to their temperature characteristics, SiNWTs show higher stability to ambient temperature variations compared with GeNWTs, which in turn demonstrate a higher sensitivity in all cases compared with SiNWT. In addition, SiNWTs outperform GeNWTs in terms of SS and Vth and demonstrate a faster switching speed and lower leakage current given that the values of SS are very close to the ideal state and high threshold voltages. SiNWTs also achieve a high DIBL level in certain cases, which is considered acceptable for most channel dimensions. The impact of changing the gate length on the behaviour of NWTs is very obvious, and varying the oxide thickness demonstrates the lowest impact. SiNWTs have high potential to be applied as temperature nanosensors due to their electrical and temperature stability.